On the Deformation Retract of Eguchi-Hanson Space and Its Folding - H. Rafat; Nasr Ahmed (Advances in Mathematical Physics)
We introduce the deformation retract of the Eguchi-Hanson space using Lagrangian equations. The retraction of this space into itself and into geodesics has been presented. The deformation retract of the Eguchi-Hanson space into itself and after the isometric folding has been discussed. Theorems concerning these relations have been deduced.